2021
DOI: 10.1007/s12662-021-00766-y
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: The impact of COVID-19 Delta variant home confinement on student physical health literacy—a call for awareness in physical education

Abstract: During the coronavirus disease 2019 (COVID-19) Delta variant wave of the pandemic, governments implemented health orders and policies that included citizens in lockdowns and confined to the home. These health orders and home confinement reduced children’s time for engagement in physical activity and access to supervised, structured physical education (PE) lessons. To understand the potential impact on the physiological aspects of children’s physical health literacy, one must understand the adverse consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To reduce the occurrence of this trend, he believes that this purpose can be achieved by storing and analyzing the data of students' health [9]. Sortwell and Ramirez-Campillo combined examples of the 2019 coronavirus disease (COVID-19) delta variant to detect physical health indicators in children [10]. For students' physical health detection, there is a small amount of literature based on neural network research, but because the factors affecting students' physical fitness are diverse, to measure more accurately and effectively, it is obvious that DNN can meet this demand.…”
Section: Related Workmentioning
confidence: 99%
“…To reduce the occurrence of this trend, he believes that this purpose can be achieved by storing and analyzing the data of students' health [9]. Sortwell and Ramirez-Campillo combined examples of the 2019 coronavirus disease (COVID-19) delta variant to detect physical health indicators in children [10]. For students' physical health detection, there is a small amount of literature based on neural network research, but because the factors affecting students' physical fitness are diverse, to measure more accurately and effectively, it is obvious that DNN can meet this demand.…”
Section: Related Workmentioning
confidence: 99%
“…Nowadays, most of the world are facing a high risk pandemic that has a huge negative impact on all areas including physical education in elementary schools to universities (López-Valenciano, Suárez-Iglesias, Sanchez-Lastra & Ayán, 2021;Roe, Blikstad-Balas & Dalland, 2021;Fang, Teng & Wang, 2021). Data reported that the COVID-19 pandemic caused athletes and teachers to carry out offline teaching while some people claimed that online teaching had various obstacles and did not provide optimal results (Jumareng et al, 2021;Sortwell & Ramirez-Campillo, 2022), which could led to a significant decrease in their talent related to physical literacy (Duclos-Bastías, Vallejo-Reyes, Giakoni-Ramírez & Parra-Camacho 2021; Young, O'Connor, Alfrey & Penney, 2021). According to Liu & Chen (2021) (2021), physical literacy in the context of physical education and sports has a concept as knowledge, motivation, self-efficacy and physical competence for active and sustainable involvement in lifelong physical activity (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While students’ engagement in physical activity should be encouraged, particularly in light of recent research ( Dunton et al, 2020 ) noting global physical activity decreases during Covid-19, such approaches are rarely accompanied by an educative purpose or themes ( Dyson, 2014 ), and do not foster sustainable learning or promote behaviour change. In the Covid-19 experience studies to date, some teachers show little evidence of thought to fundamental movement skills, movement competence and motivation, young people's personal and social skill development, and health literacy development for their wellbeing ( McCaffery et al, 2020 ; Sortwell and Ramirez-Campillo, 2022 ). These core elements and many others represent the content strands and descriptors that underpin the HPE curriculum ( ACARA, 2020 ), thus providing a framework for the education and development of all school students in the HPE learning area.…”
Section: Introductionmentioning
confidence: 99%